Satisfaction level and challenges in payments transaction encountered by graduate school students and procedure recommendations - Mancenido, Mitzi, Sofia M.; Sasoza, Norjaen L.; Torres, Angelo Josh Q.; Villanueva, Shirley Ann F. (b)
This research focuses on how satisfied graduate school students are with their school{92}s payment system and what problems they face. We asked graduate students about paying for things like tuition and fees. The goal was to find what makes paying difficult and to recommend a policy and procedures to make it better. Our findings show that many students are satisfied but still encountered challenges while paying their tuition or fees. They reported common challenges such as systemic and procedural deficiencies where the inefficient on site and digital transaction processes hinders satisfaction of the students, including the lack of post transaction communication and transparency. Another findings talks about the proposed solutions for a modernized payment ecosystem where the institution should continue on with investment in integrated digital infrastructure and tools along with the policy and procedural for clarity and efficiency to its students. Overall, the students were very satisfied with the payment system{92}s fundamental attributes particularly Service Quality, Clarity and Accuracy, and Timeliness. These consistently high ratings suggest that the system works well in delivering reliable and courteous service that meets academic deadlines. The professionalism of the staff and clarity of the payment instruction would seem to support trust by students and create a solid functional foundation for the financial function of the institution. Based on these findings, we recommend specific changes. The following suggested policy recommendations may help the institution in improving the satisfaction of the students. The proposed procedure recommendation is distributing that includes the process in payment transaction. This is a way to introduce to a wide range of students that can make payment transactions easier and faster.
Undergraduate thesis.